Enhancement in Power Conversion Efficiency of GaAs Solar Cells by Utilizing Gold Nanostar Film for Light-Trapping - Zhu, Sheng-Qing; Bian, Bin; Zhu, Yun-Feng; Yang, Jun; Zhang, Dan; Feng, Lang (Frontiers in Chemistry, 2019)
Light trapping, due to the introduction of metallic nanoparticles, has been demonstrated to enhance the photo-absorption in GaAs solar cells. In this study, we successfully synthesized gold nanostar thin film with a plenty of hot spots and obtained the notable improvement of power conversion efficiency (PCE) in single-junction and three-junction high-performance GaAs solar cells by incorporating with the poly (3,4-ethylenedioxythiophene): poly(styrenesulfonate) (PEDOT:PSS) layer, which process much stronger light trapping capability and scattering enhancement than conventional metal nanostructures. Increases of 5.2% and 3.94% in short circuit current density (Isc)) were achieved for single-junction cells and three-junction cells while the enhancement in cell PCE is 3.85% and 2.50%, respectively. The relationship between the optical characteristics, the distribution density of the gold NSs and the performance of GaAs solar cells were systemically investigated.